Application of lisinopril in the complex correction of the vessel wall antiaggregational activity in patients with arterial hypertension and metabolic syndrome who suffered from occlusion of the eye vessels - O A Danilenko (RUDN Journal of Ecology and Life Safety, 2010)
The aim of this work is to investigate the possibilities of correction of a vessel wall antiaggregational activity in patients with arterial hypertension and metabolic syndrome, who suffered from occlusion of eye vessels by using complex therapy including lisinopril, Pioglitason and non-medic correction. It's found out that in such patients this complex is able to normalize the vessel wall antiaggregational activity during 4 months of therapy. The achieved results were observed even during not full non-medical correction in conditions of adverse ecology.